Механізм судового захисту прав та свобод людини і громадянина у криминальному провадженні - Назаров, В.В. (Часопис Київського університету права, 2009)
В статье автор исследует роль суда в защите прав и свобод человека и гражданина, раскрывает виды судебного контроля, право на обжалование действий и решений органов дознания и досудебного следствия, проблемы разграничения судебного контроля и прокурорского надзора за досудебным расследованием. In the article an author investigates the role of court in defence of rights and freedoms of man and citizen, exposes the types of judicial control, right on the appeal of actions and decisions of organs of inquest and pre-trial investigation, problem of differentiating of judicial control and directorate of public prosecutions after pre-trial investigation.